Management of the psychosocial care network: an integrative review (Research, Society and Development, 2021)
Objective: to analyze in the literature, how the psychosocial care network is management and the participants of this process, taking into account social participation through the National Health Council. Method: Integrative Review, which is based on the six phases established by Mendes, Silveira and Galvão, using the PCC strategy for the formulation of the guide question. Results: A total of 10 articles discussion were chosen: Through the analysis of the articles through intensive reading, the following categories were formulated: Process of management of the Psychosocial Care Network and Participants of the management process. Conclusion: Managers, multidisciplinary teams and users need to work together to manage the network so that there is the establishment of goals and planning that meet its needs.